Shorter anogenital distance correlates with undescended testis: a detailed genital anthropometric analysis in human newborns - Jain, Viral G.; Singal, Arbinder Kumar (Human reproduction (Oxford), 2013)
STUDY QUESTION Are the anogenital distance (AGD) and stretched penile length (SPL) shorter in human newborn males with cryptorchidism? SUMMARY ANSWER AGD is significantly shorter in boys with undescended testis (UDT) and this correlation may indicate that both have a common antecedent early in gestation. WHAT IS KNOWN ALREADY Animal studies have reported a critical time period during early gestation termed the male programming window (MPW) where androgen deficiency results in reduced AGD and penile length, as well as cryptorchidism and hypospadias. Two pilot human studies have explored this association but these studies were small and heterogeneous with regard to age, race and had selection bias. STUDY DESIGN, SIZE, DURATION A prospective descriptive study involving measurement of AGD and SPL at birth in a racially homogenous sample of 1154 consecutive newborns was performed over a period of 6 months. All measurements were taken by a single trained observer (V.J.). PARTICIPANTS/MATERIALS, SETTING, METHODS All consecutively born male infants at a community hospital were classified as having descended and or UDT. Testicular position in the undescended group was graded as high scrotal, inguinal or non-palpable. AGD (from the centre of anus to the junction of the smooth and rugated skin of scrotum) and SPL were measured. The AGD index (AGDi) was calculated by dividing AGD by cube root of birthweight. MAIN RESULTS AND THE ROLE OF CHANCE Of the 1154 infants examined, 624 were males and 71 had UDT. AGD was significantly shorter in infants with UDT when compared with infants with descended testis (mean ± SD; 2.21 ± 0.36 versus 2.56 ± 0.31 cm; P < 0.001). AGDi was also significantly shorter in infants with UDT (mean ± SD; 1.68 ± 0.27 versus 1.81 ± 0.20 cm/kg−3; P < 0.001). Significance was maintained even when preterm (P < 0.001) and low birthweight boys (LBW) (P < 0.001) were excluded. SPL was also significantly shorter in infants with UDT (Mean ± SD; 3.08 ± 0.52 versus 3.31 ± 0.38 cm; P < 0.001) but the significance was not maintained when preterm (P = 0.119) and LBW boys (P = 0.666) were excluded. Birthweight, gestational age and length adjusted regression models showed significantly shorter AGD in infants with UDT, but SPL was not different. Infants with higher position of testis appeared to have a shorter AGD and SPL but the correlation did not reach statistical significance. No difference in AGD or SPL was noted between boys with unilateral and bilateral UDT. LIMITATIONS, REASONS FOR CAUTION The present study did not include data pertaining to maternal or newborn health status. Also parental drug exposure or occupational exposures to endocrine-disrupting chemicals was not studied. These may possibly affect genital anthropometric measurements. WIDER IMPLICATIONS OF THE FINDINGS The study strengthens the hypothesis of existence of MPW in humans. Shorter AGD in cryptorchid infants may reflect the effect of androgen disruption or deficiency during MPW. AGD may be a more reliable non-invasive marker of androgen action during MPW than SPL to predict reproductive outcomes in humans. STUDY FUNDING/COMPETING INTEREST(S) Supported by Hypospadias Foundation, India. The authors have no conflict of interest to declare.